The Relationship between Cariogenic Food Consumption and the Incidence of Dental Caries in Grade 5 Children of Public Elementary School 10 in Kampung Baru - Prastyo, Eko; Belangi, Siska Putri; Sahalessy, Yona; Listina, Osie; Yulis, Dian Meiliani; Utari, Utari (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
Cariogenic foods are foods that contain lots of carbohydrates, are sticky and break down easily in the mouth. Dental caries is damage to hard tooth tissue caused by acids contained in carbohydrates through microorganisms contained in saliva. The aim of this study was to determine the relationship between consumption of cariogenic foods and the incidence of dental caries in grade 5 children at SD Negeri 10 Kampung Baru r. The type of research used is analytical descriptive research using a cross sectional design. The population in this study was 95 people and the sampling technique used Consecutive Sampling technique, the total sample was 77 respondents. Data was collected using a questionnaire, the collected data was then processed and analyzed using Microsoft Excel and the SPSS program. Data analysis includes univariate analysis by looking for frequency distributions, bivariate analysis with the Chi-Square test (α=0.05) to determine the relationship between variables. The research results show that based on the results of the Chi-Square test, the value obtained is p=0.003. The conclusion of this research is that there is a relationship between the consumption of cariogenic foods and the incidence of dental caries in grade 5 children at SD Negeri 10 Kampung Baru.